Development of antibody fragments for targeted PET- and single EV-imaging - Korkea-Aho, Roope (My University, 2024)
Extracellular vesicles (EVs) are a diverse group of lipid structures that all cells secrete. They are found in many bodily fluids, and they transport cargo, such as lipids, proteins and nucleic acids. EVs are involved in signaling and can also be used as a biomarker for many diseases, such as cancer. EVs are an emerging field in research, but the high diversity of the group has been a challenge in studying communication between cells. That is why single EV-imaging techniques have been developed. Other imaging techniques, such as positron emission tomography (PET) -imaging have also become common place in cardiovascular disease diagnosis. The aim of the project was to find high affinity antibody fragments against tetraspanin and FABP3 target antigens using a nanobody or a Fab library which could be used in PET- and single EV-imaging. In this project, phage display technology was used to find high affinity binders against target antigens and potential binders were discovered using ALP-ELISA. Characterization of the best binders were done using bio-layer interferometry and immunoassays. After multiple rounds of panning, several potential binders for PET-imaging were found during the screening process. Clone F10 was found to have a KD-value of 5.05 nM and clone D12 a KD-value of 0.93 nM. In the end, high affinity Fab binders were found using a synthetic human Fab phage library against a PET-imaging target antigen which could be used in cardiovascular imaging.
Keywords: extracellular vesicles, fatty acid-binding protein 3, imaging, phage display, tetraspanin, fragment antigen-binding, antibody characterization